Corrosion Behavior of Commercial Alloys in LiCl–KCl Molten Salt Containing EuCl3 - Chang, Shuangshuang; Jia, Yanhong; Du, Xin; Guo, Shaoqiang (Frontiers in Materials, 2022)
Pyroprocessing of spent nuclear fuels uses the LiCl–KCl molten salt as an electrolyte, which contains dissolved fission products and can be very corrosive to the structural alloys. This study investigates the effect of EuCl3 on the corrosion behavior of four commercial alloys: Haynes C276, Inconel 600, Incoloy 800, and 316L stainless steel. Static immersion tests and electrochemical polarization measurements were carried out in molten LiCl–KCl salts with and without EuCl3 additives at 500°C. The results showed that the presence of EuCl3 caused the severe dissolution of Ni, Fe, and Cr from alloys, accompanied by the cathodic reduction of EuCl3 to EuCl2. All alloys suffered from intergranular dissolution and cracking, with additional pitting and void attacks for Incoloy 800 and 316L stainless steel.